Challenges in Saudi Universities Shift Toward a Knowledge Society - Alshayea, Ali S. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Higher education in Saudi Arabia is facing several challenges posed by a set of transformations in society in general, and the economy in particular. As economies become increasingly knowledge-based, universities bear the burden of helping the community transform into a knowledge society. This paper focuses on the most important challenges facing Saudi universities as they shift toward becoming contributors to a knowledge society. Using a descriptive analytical approach, data was collected from several studies and published statistics. A range of challenges was discovered, the most important of them are a heavy reliance on government funding, poor productivity of faculty members, the gap between the outputs of universities and the labor market, the absence of strategic planning for higher education, the absence of a national strategy for scientific research, and the weakness of the relationship between undergraduate majors and the needs of the community.